A magnesium alloy composite material containing multivalent elements and a method of manufacturing the same
Patent Information
- Application Number
- CN202611052194.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-13
AI Technical Summary
但是并未对含有多价态元素的镁合金复合材料这一改进点进行特别深入的保护
[0015](1)本申请的多价态元素不仅包括轻稀土元素,还包括过渡金属元素;本申请的多价态元素可以提供多级电化学电位梯度,驱动溶解反应在不同阶段持续进行;使得溶解更彻底、无残留,更加可控;
Abstract
Description
Technical Field
[0001] This application relates to a magnesium alloy composite material containing elements with multiple valence states and a method for preparing it. Background Technology
[0002] In existing technologies, the dissolution driving force of soluble magnesium alloy composites is relatively singular, relying solely on the formation of a galvanic cell by a high-potential second phase, lacking a multi-level electrochemical driving system. When the second phase is unevenly distributed or locally depleted, the driving force of the dissolution reaction will weaken or even terminate, resulting in incomplete dissolution or the formation of residues.
[0003] The applicant's prior application 202610679250.5 is the foundational patent for the improvements made in this application, and that patent proposes several directions for technical improvements. However, it does not provide particularly in-depth protection for the improvement point of magnesium alloy composite materials containing multivalent elements. Summary of the Invention
[0004] This application provides a magnesium alloy composite material containing multivalent elements. By utilizing the multivalent electrochemical properties of multivalent elements, and introducing compounds or salts of different valence states, elements of different valence states coexist in the finished material, forming a multi-level electrochemical driving system to promote the dissolution of the magnesium alloy composite material.
[0005] This application relates to a magnesium alloy composite material containing multivalent elements, comprising a magnesium matrix and multivalent elements to construct a multi-level electrochemical potential gradient. The multivalent elements are at least one of multivalent transition metal elements or light rare earth elements, and exist in at least one of the following forms: elemental metal, intermediate alloy formed by elemental metal and magnesium matrix, salt, oxide, coordination compound, complex. The multivalent elements account for 0.05-10% by weight in the magnesium alloy composite material.
[0006] When multivalent elements coexist with a magnesium matrix in an electrolyte environment, there is a difference in the standard electrode potential between the half-cell reaction of the multivalent elements and the half-cell reaction of Mg. Generally speaking, the metal electrode potential of the multivalent elements, or the electrode potential of the multivalent compounds, is at least 0.1 volts higher than that of magnesium. This allows the multivalent elements to drive the oxidation and dissolution of the surrounding Mg matrix while undergoing their own reduction reaction, forming a spontaneous “reduction-oxidation” coupled electrochemical cycle.
[0007] The multivalent elements are adsorbed and coated with porous inert materials to ensure that the rare earth valence states do not undergo unexpected changes during the preparation process. It also includes pre-added heterogeneous components as non-spontaneous nucleation centers. These pre-added heterogeneous components are uniformly distributed at grain boundaries and within grains, serving as heterogeneous nucleation centers to promote the development of equiaxed crystals. The pre-added heterogeneous components are selected from at least one of Mn, Si, Cr, Sn, Ti, Zr, La, Ce, Pr, Nd, Sm, and Eu, or are microparticles of porous adsorption coating materials, or additives that can significantly reduce the magnesium precipitation free energy and phase transformation surface tension. The total addition amount is 0.05-15% of the total alloy weight. The pre-added heterogeneous components can be added as metals, as intermediate alloys, or as metal salts. The magnesium alloy composite material of this application has a dissolution rate of 10-350 mg / cm³ in pure water or an electrolyte solution with a mineralization of up to 250,000 ppm at room temperature. 2 ·h. At least one of the multivalent elements is added in at least two phases with different valence states, or is added in a single valence state and exists in at least two valence state phases in subsequent smelting or when in contact with water or electrolyte.
[0008] This application also relates to a method for preparing a magnesium alloy composite material, wherein the magnesium alloy composite material is as described above, and the preparation method includes the following steps:
[0009] (1) Additives containing multivalent elements are adsorbed and coated into microcapsules using porous inert materials;
[0010] (2) Heat the alloy until all components melt, add multivalent element additives and porous inert material microcapsules to the molten magnesium matrix, melt all components together, and allow the microcapsules to be gradually released in the melt;
[0011] (3) Heating causes the components to alloy, and the added microcapsule components are distributed at the particle boundaries, forming different valence states and different potential gradient structures between the matrix phase particles and the porous additive capillary.
[0012] (4) Semi-continuous casting to prepare casting rods or billets.
[0013] The preparation method further includes at least one of homogenization, extrusion, forging deformation, and aging treatment.
[0014] The magnesium alloy composite material containing multivalent elements according to this application has the following technical advantages:
[0015] (1) The multivalent elements in this application include not only light rare earth elements, but also transition metal elements; the multivalent elements in this application can provide multi-level electrochemical potential gradients to drive the dissolution reaction to continue at different stages; making the dissolution more thorough, without residue, and more controllable;
[0016] (2) This application utilizes the “reduction-oxidation” coupled electrochemical cycle formed between multivalent elements and the magnesium matrix, so that phases containing rare earth elements such as Ce act as cathode promoters and are continuously reduced, while Mg acts as anode and is continuously oxidized and dissolved.
[0017] (3) It can achieve valence state protection and realize the wide distribution of electrochemical potential difference in finished materials. The multi-level nature of the dissolution driving force avoids the common problem of driving force decay in single valence state systems. Detailed Implementation
[0018] Where there is no conflict, the embodiments and features described in this application may be combined arbitrarily with each other.
[0019] This application, as an extension of patent No. 202610679250.5, delves deeper and provides more refined protection regarding the use of the multivalent electrochemical properties of light rare earth elements to drive the dissolution of magnesium alloy composite materials. The following explanation uses light rare earth elements as an example; those skilled in the art will understand that multivalent transition metal elements can also be used in this application.
[0020] This application relates to a magnesium alloy composite material containing multivalent elements, comprising a magnesium matrix and multivalent elements to construct a multi-level electrochemical potential gradient. The multivalent elements include multivalent transition metals and light rare earth elements, existing in at least one form selected from elemental metals, intermediate alloys formed from elemental metals and the magnesium matrix, salts, oxides, coordination compounds, and complexes. When the multivalent elements coexist with the magnesium matrix in an electrolyte environment, a difference in standard electrode potential exists between the half-cell reaction of the multivalent elements and the half-cell reaction of Mg. This allows the multivalent elements to undergo their own reduction reaction while simultaneously driving the oxidative dissolution of the surrounding Mg matrix, forming a spontaneous "reduction-oxidation" coupled electrochemical cycle. The amount of multivalent elements added is 0.05-10% by weight.
[0021] Multivalent elements include any one or more mixed elements: transition metal elements, salts, complexes, and oxides of transition metals in different valence states; light rare earth metal elements, such as La, Ce, Pr, Nd, Sm, Eu, etc., and their salts, oxides, and complexes in different valence states. Multivalent elements can be coated into porous, high specific surface area materials through adsorption, smelting, sintering, etc., and then added to a magnesium alloy composite material smelting furnace to prepare magnesium alloy composite materials containing multivalent elements. The multivalent added elements are pre-prepared and added to the porous adsorption coating material at a ratio of 1:10 to 5:1 by weight. The metal electrode potential of the multivalent element, or the electrode potential of multiple valence compounds in aqueous electrolyte, is at least 0.1 volts higher than the electrode potential of magnesium.
[0022] The multivalent elements can be adsorbed and coated with porous inert materials to ensure that the rare earth valence states do not undergo unexpected changes during the preparation process. It also includes pre-added heterogeneous components that serve as non-spontaneous nucleation centers. These pre-added heterogeneous components are uniformly distributed at grain boundaries and within grains, acting as heterogeneous nucleation centers to promote the development of equiaxed crystals. The pre-added heterogeneous components are selected from at least one of Mn, Si, Cr, Sn, Ti, Zr, La, Ce, Pr, Nd, Sm, and Eu, or are microparticles of porous adsorption coating materials, or additives that can significantly reduce the magnesium precipitation free energy and phase transformation surface tension. The total addition amount is 0.05-15% of the total alloy weight. The pre-added heterogeneous components can be added as metals, as master alloys, or as metal salts.
[0023] This application utilizes the multi-valence electrochemical properties of light rare earth elements to simultaneously contain light rare earth intermetallic compounds and / or light rare earth compounds with different valence states in the finished material, constructing a multi-level, dynamically stable electrochemically driven system. Light rare earth elements can be added in the form of metallic elements, intermediate alloys, or compounds containing light rare earth elements. Different added forms correspond to different valence state distributions and release characteristics. By rationally combining light rare earth compounds with different valence states, a multi-level electrochemical potential gradient is constructed, ensuring that the dissolution reaction is driven by appropriate electrochemical forces at different stages, avoiding the attenuation of driving forces that may occur in a single-valence system. Kaolin / diatomite coating is used to protect the variable-valence rare earth compounds, or a protective nucleation environment is constructed by pre-installing heterogeneous components to ensure that the rare earth valence states do not undergo unexpected changes during the smelting process.
[0024] According to this application, a magnesium alloy composite material containing elements with multiple valence states has the following key technologies:
[0025] 1. Multiple ways to add forms
[0026] Light rare earth elements can be added to the melt in at least one of the following forms:
[0027] (1) Metallic elemental forms (such as Ce, La, and Sm metals)
[0028] (2) Intermediate alloy form (e.g., Mg-RE intermediate alloy)
[0029] (3) Salts containing light rare earth elements (such as chlorides CeCl3, SmCl3, etc.)
[0030] (4) Oxide forms containing light rare earth elements (such as CeO2, Sm2O3, etc.)
[0031] 2. Multiple price-driven mechanisms
[0032] Light rare earth elements such as Ce, La, and Sm exhibit stable multi-valence characteristics in acidic, alkaline, and neutral media (including various complex fracturing fluids and flowback fluid environments in oil and gas wells).
[0033]
[0034]
[0035] Taking Ce as an example, its electrochemical characteristics are as follows:
[0036] Ce 4+ / Ce 3+ The standard electrode potential of the redox couple in an acidic medium is approximately +1.74V (strong oxidizing agent).
[0037] Ce 3+ / Ce 2+ The thermochemical reduction potential of the redox couple is approximately -3.76V (strong reducing power).
[0038] When Ce with different valence states coexists with a Mg matrix in an electrolyte environment, the standard electrode potential of the Ce-related half-cell reaction differs from that of the Mg half-cell reaction (Mg... 2+ The difference between the standard electrode potential of Mg (approximately -2.37V) and Ce causes Ce to undergo self-reduction reactions (such as Ce...). 4+ +e - →Ce 3+ Simultaneously, it drives the oxidative dissolution of the surrounding Mg matrix (Mg→Mg). 2+ + 2e - This forms a spontaneous reduction-oxidation coupled electrochemical cycle.
[0039] 3. Price Status Protection
[0040] Porous inert materials such as kaolin and diatomaceous earth are used to adsorb and coat rare earth compounds to protect them, or heterogeneous components are pre-placed and retained to construct a protective nucleation environment to ensure that the valence state of rare earths does not change unexpectedly during high-temperature smelting.
[0041] The pre-added heterogeneous component can be an additive capable of significantly reducing the magnesium precipitation free energy and phase transformation surface tension, with a total addition amount of 0.05-15% of the total alloy volume. It can be selected from at least one of Mn, Si, Cr, Sn, Ti, Zr, La, Ce, Pr, Nd, Sm, and Eu, or microparticles of the porous adsorption coating material, or an additive capable of significantly reducing the magnesium precipitation free energy and phase transformation surface tension. The addition method includes adding as a metal, as an intermediate alloy, or as a metal salt. Furthermore, the microparticles of the porous adsorption coating material may also serve as heterogeneous nucleation centers.
[0042] After the addition of light rare earth elements to form intermetallic compounds, these heterogeneous components act as non-spontaneous nucleation centers, promoting the development of equiaxed crystals. This results in the widespread and uniform distribution of light rare earth intermetallic compounds throughout the finished material, achieving uniform, complete, and continuous controlled dissolution. The extensive pre-establishment of heterogeneous nucleation centers also plays a role in grain refinement, thereby improving the mechanical properties of the alloy and enhancing the strength and plasticity of the material. The addition can be done as a metal; as an intermediate alloy such as magnesium zirconium, magnesium manganese, or magnesium titanium; or as a metal salt such as manganese chloride. It can be added to a melting furnace along with other components, alloyed, and then cast, or it can be added after other components have melted. The specific method depends on the process, yield, and state of the additives. The magnesium alloy composite material obtained in this application can dissolve at a rate of up to 350 mg / cm³ in a 3% KCl-water mixture at 90°C. 2 ·h.
[0043] This application also relates to a method for preparing a magnesium alloy composite material, which is the magnesium alloy composite material as described above, and the preparation method includes the following steps:
[0044] (1) Additives containing multivalent elements are adsorbed and coated into microcapsules using porous inert materials;
[0045] (2) Heat the alloy until all components melt, add multivalent element additives and porous inert material microcapsules to the molten magnesium matrix, melt all components together, and allow the microcapsules to be gradually released in the melt;
[0046] (3) Heat to, for example, 720-780℃ to alloy the components, so that the added microcapsule components are distributed at the particle boundary, and the matrix phase particles and porous additives in the capillary form different valence states and different potential gradient structures; thereby forming a complex electrochemical system between the half-cell potential and the capillary surface potential to promote the rapid dissolution of the magnesium alloy composite matrix.
[0047] (4) Semi-continuous casting to prepare cast bars or billets. It also includes at least one of homogenization, extrusion, forging and rolling deformation, and aging treatment.
[0048] Example 1: Addition of multivalent Ce compounds
[0049] The following components were selected by mass percentage: Mg 92%, Zn 4%, CeCl3 2%, CeO2 1%, and Zr 1%. CeCl3 and CeO2 were pre-prepared into microcapsules by adsorption and coating with kaolin, with a CeCl3 coating thickness of 80 μm and a CeO2 coating thickness of 40 μm, to achieve phased release during the melting and solidification processes.
[0050] Melting process: CeCl3 microcapsules are added at 720℃ and held for 20 min to allow partial release; CeO2 microcapsules are added at 760℃ and held for 15 min; semi-continuous casting cooling rate is 40℃ / s; homogenization is carried out at 470℃ for 14 h; extrusion ratio is 14:1 and temperature is 370℃; aging is carried out at 180℃ for 36 h.
[0051] Valence characterization: XPS analysis showed that Ce was also detected in the finished material. 3+ (approximately 60% of total Ce) and Ce 4+ (Approximately 30% of total Ce), with another 10% in the form of intermetallic compounds Mg. 12 Ce exists in the Ce form. During the smelting process, adsorption coating protects and controls the Ce valence state change rate within ±15%, while in the non-adsorption-coated control sample, Ce... 3+ Almost all of it was oxidized to Ce 4+ .
[0052] Electrochemical performance: Atomic force microscopy revealed that the second phase of this alloy exhibited a value of -1.52V compared to the matrix phase, significantly higher than the single-valence control sample (-V). 3+ / Ce 4+ The presence of variable valence pairs provides an additional driving force for electrochemical dissolution.
[0053] Solubility: Dissolution rate in 3% KCl at 93℃: 120 mg / cm³ 2 The dissolution curve of the control sample was linear (constant rate) and the dissolution curve of the control sample was exponential (the rate gradually decreased).
[0054] Example 2: LaCl3+Sm2O3 composite variable valence system
[0055] The composition by mass percentage is: Mg 91%, Al 5%, LaCl3 1.5%, Sm2O3 1.5% (Sm exists in the +3 oxidation state), and Ca 1%. LaCl3 is coated with diatomaceous earth (shell thickness 30μm), and Sm2O3 is partially coated with kaolin (shell thickness 20μm).
[0056] The smelting process is the same as in Example 2-1, with homogenization at 490℃ for 12 hours, an extrusion ratio of 16:1, a temperature of 385℃, and aging at 200℃ for 20 hours.
[0057] Valence characterization: XPS analysis shows that La is characterized by La 3+ and intermetallic compounds Mg 17 La2 coexists, Sm in Sm form 3+ and a small amount of Sm 2+ It exists in form. Sm 2+ / Sm 3+ A stepped potential difference is formed between the valence pair (standard electrode potential approximately -3.76V vs matrix phase) and Mg2+ / Mg (-2.37V).
[0058] Solubility: Dissolution rate in 3% KCl at 93℃: 140 mg / cm³ 2 The dissolution rate exhibits a good linear relationship with temperature, and the dissolution behavior is highly controllable. The calculated activation energy for dissolution at different temperatures is 52.3 kJ / mol, which is lower than that of traditional Ni / Cu soluble magnesium alloy composites (approximately 68 kJ / mol), verifying the role of the light rare earth variable valence system in lowering the reaction energy barrier.
[0059] Example 3: Effect of different valence state combinations on dissolution behavior
[0060] By fixing the basic component Mg-4Zn-3RE (RE being a combination of Ce, La, and Sm), the proportions of compounds with different valence states were adjusted to investigate the effect of valence state combinations on dissolution behavior.
[0061] A 90:10 138 Attenuation type 96 Yes (approximately 8%) B 60:40 155 near-linear 72 Trace amount (<1%) C 30:70 168 Acceleration 58 none D 20:80 182 Acceleration 48 none
[0062] The results show that: Ce 4+ Samples with higher proportions (C, D) dissolved faster and more completely, which is related to Ce. 4+ / Ce 3+ The high reduction potential (+1.74V) of the redox couple is closely related, as it acts as a strong oxidizing agent and can more effectively drive the oxidative dissolution of the Mg matrix. Optimal valence state ratio (sample C: 30% Ce) 3+ 70% Ce 4+ It achieves a balance between rapid dissolution and complete dissolution.
[0063] Although the embodiments disclosed in this application are as described above, the content is merely for the purpose of facilitating understanding of this application and is not intended to limit this application. Any person skilled in the art to which this application pertains may make any modifications and changes in the form and details of the implementation without departing from the spirit and scope disclosed in this application; however, the scope of patent protection of this application shall still be determined by the scope defined in the appended claims.
Claims
1. A magnesium alloy composite material containing elements in multiple valence states, comprising a magnesium matrix, characterized in that, It also includes multivalent elements to construct multi-level electrochemical potential gradients. The multivalent elements are at least one of multivalent transition metal elements or light rare earth elements, and exist in at least one of the following forms: metallic element, intermediate alloy formed by metallic element and magnesium matrix, salt, oxide, coordination compound, complex. The multivalent elements account for 0.05-10% by weight in the magnesium alloy composite material.
2. The magnesium alloy composite material according to claim 1, characterized in that, When multivalent elements coexist with the magnesium matrix in an electrolyte environment, there is a difference in the standard electrode potential between the half-cell reaction of the multivalent elements and the half-cell reaction of Mg. This causes the multivalent elements to drive the oxidation and dissolution of the surrounding Mg matrix while undergoing their own reduction reaction, forming a spontaneous "reduction-oxidation" coupled electrochemical cycle.
3. The magnesium alloy composite material according to claim 1 or 2, characterized in that, The multi-valence elements are adsorbed and coated with porous inert materials to ensure that the valence state of rare earth elements does not undergo unexpected changes during the preparation process.
4. The magnesium alloy composite material according to claim 1 or 2, characterized in that, It also includes pre-added heterogeneous components that serve as non-spontaneous nucleation centers. These pre-added heterogeneous components are uniformly distributed at grain boundaries and within grains, serving as heterogeneous nucleation centers to promote the development of equiaxed crystals.
5. The magnesium alloy composite material according to claim 4, characterized in that, The pre-added heterogeneous components are selected from at least one of Mn, Si, Cr, Sn, Ti, Zr, La, Ce, Pr, Nd, Sm, and Eu, or are microparticles of porous adsorption coating materials, or are additives that can significantly reduce the magnesium precipitation free energy and phase transformation surface tension, with a total addition amount of 0.05-15% of the total alloy amount.
6. The magnesium alloy composite material according to claim 5, characterized in that, The method of adding the pre-added heterogeneous components includes adding them as metals, as intermediate alloys, or as metal salts.
7. The magnesium alloy composite material according to any one of claims 1-2 and 5-6, characterized in that, The magnesium alloy composite material has a solubility rate of 10-350 mg / cm³ in pure water or an electrolyte solution with a salinity of up to 250,000 ppm at room temperature. 2 ·h.
8. The magnesium alloy composite material according to any one of claims 1-2 and 5-6, characterized in that, At least one of the multivalent elements is added in at least two phases with different valence states, or is added in a single valence state and then exists in at least two valence state phases during subsequent smelting or when in contact with water or electrolyte.
9. A method for preparing a magnesium alloy composite material, characterized in that, The magnesium alloy composite material is the magnesium alloy composite material according to any one of claims 1-8, and its preparation method includes the following steps: (1) Additives containing multivalent elements are adsorbed and coated into microcapsules using porous inert materials; (2) Heat the alloy until all components melt, add multivalent element additives and porous inert material microcapsules to the molten magnesium matrix, melt all components together, and allow the microcapsules to be gradually released in the melt; (3) Heating causes the components to alloy, and the added microcapsule components are distributed at the particle boundaries, forming different valence states and different potential gradient structures between the matrix phase particles and the porous additive capillary. (4) Semi-continuous casting to prepare casting rods or billets.
10. The preparation method according to claim 9, characterized in that, The preparation method further includes at least one of homogenization, extrusion, forging deformation, and aging treatment.